Pterygium excision followed by sutureless and gluefree infero-temporal conjunctival autograft - Poonam Bhargava; Anju Kochar; Rashmi Joshi (Delhi Journal of Ophthalmology)
Introduction: There are various methods available at present to reduce the recurrence after pterygium excision and the one in the trend is the sutureless and gluefree conjunctival autografting which is gaining popularity for it’s ease and better results than other methods. Objective: To study the efficacy and complications of sutureless and glue free conjunctival autografting for the management of primary pterygium over a period of 7 years. Material and Methods: A prospective, interventional case study was carried out over 300 patients having primary pterygium. Pterygium excision followed by conjucntival autografting without using any suture and glue was performed in all the patients which was followed by bandaging for 24 hours. The patients were followed up post-operatively on day 1, week 1, week 2, month 1, 2 and 3 and for recurrence upto 1 year if possible. They were examined for haemorrhage, graft edema, graft encrochment on cornea, visual acuity, refractory changes and recurrence. Results: The age of cases varied between 21 to 60 years. 59.33% of which were male. Subconjunctival haemorrhage was seen in 23.6% on day-1 which reduced to 8.33% at day 15 and no subconjunctival haemorrhage at the end of month 1. Serous exudate was present in 26 cases (8.67%) on day-1, which subsided within two weeks without any intervention. Graft displacement was seen in 16 patients (5.33%) and encrochment on cornea was seen in 28 patients (9.33%), tenon cyst was seen in 3 patient (1%) and recurrence was seen in 3 patients (1.0%). In 3 cases displaced graft became avascular hence were removed. Visual acuity improvement was noted in 278 patients. Conclusion: Sutureless and glue free conjunctival autograft following pterygium excision is a safe, effective and economical option for the management of primary pterygium. Inferior conjunctival graft saves the superior conjunctiva for the future glaucoma surgery if it is required.